Implementasi Tanggung Jawab Pelaku Usaha Apotek Terhadap Konsumen Atas Peredaran Vaksin Palsu Di Kecamatan Sailkota Pekanbaru Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Ilham Rijab; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
So far, both food products in the form of raw and ready-to-eat ingredients and drinks with a variety of flavors and colors have been circulating widely on the market. The number of circulating products requires strong control from the government and related parties to ensure that food products on the market meet the proper standards and labeled halal for consumption. Therefore, consumers have the right to get information about the product content, ingredients made and halal products. will be consumed.This type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted research in Pekanbaru City. The reason the author chose the research location in Pekanbaru is because there are still many business actors who have not included a halal label on the goods being traded. While the population and sample are the Chairperson of the Indonesian Ulema Council (MUI) of Riau Province, Pekanbaru Breadtalk Employees and Pekanbaru Breadtalk Consumers. Data sources used are primary data and secondary data. Data collection techniques in this study were interviews, questionnaires, and literature review.The conclusions that can be obtained from the results of the study are: First, the factors underlying the producers who do not carry out halal certification of their products in the city of Pekanbaru consist of ignorance and lack of understanding of business actors regarding the existence of Law Number 33 of 2014 concerning Halal Product Guarantee, Actors Businesses Not Knowing the Procedures for Registering Halal Certification, Businesses that are Goed by Business Actors are still on a Small Business scale, Business actors assume that the raw materials used in products are Halal, business actors or producers are dishonest and commit fraud or fraud to consumers and the level of public knowledge about halal label food products is still low. Second, legal protection for consumers of products that do not have halal certification in the city of Pekanbaru is not yet maximally implemented. This is indicated by the fact that there are still many products that do not yet have certification and have not been labeled as halal. In addition, the emergence of fake halal labels that do not meet the criteria for halal or not.Keywords: Legal Protection, Consumer, Food Products, Halal Certification, Pekanbaru